Doomscrolling Spirituality On The Morality Of Islamic Students In Surabaya - Muhammad Munir; Moh. Taufiq (IJIP : Indonesian Journal of Islamic Psychology, 2024)
The impact of social media extends beyond individual experiences to profoundly influence global societal structures, economic systems, and cultural paradigms. Within the specific context of Muslim university students in Surabaya, Indonesia, social media engagement intersects uniquely with religious practice and social identity formation. The emergence of social media has fundamentally altered contemporary communication patterns, particularly through the phenomenon of "doomscrolling." This study examines the relationship between doomscrolling, spirituality, and moral development among Muslim students attending secular universities in Surabaya. Using qualitative methodology and Schutz's phenomenological framework, the research explores how these students navigate and interpret their digital experiences. Data collection comprised in-depth interviews with significant others and structured questionnaires. The analytical framework incorporated data reduction, systematic coding, and rigorous verification procedures to ensure validity. The investigation yielded four primary findings: (1) the spiritual motivations underlying doomscrolling behaviors among Muslim students; (2) the influence of doomscrolling on moral development; (3) the subjective meaning-making processes through which students interpret their doomscrolling experiences; and (4) a constructivist theoretical analysis of the interrelationship between doomscrolling, spirituality, and moral development within this specific demographic context.